Measure the impact of the age structure of the population on the gross domestic product in Iraq - حسن, رحيم كاظم (Journal of Economics and Administrative Sciences, 2013)
يهدف البحث إلى التعرف على The research aims to identify the effect ofاثر التركيب العمري للسكان على الناتج المحلي الإجمالي في العراق وتحديد الفئات العمرية من أطفال ومنتجين أي من هم في سن العمل والمسنين لأهمية ذلك لإغراض التخطيط الاقتصادي.إنeffectofeee age structure of the population on GDP in Iraq and determine the age groups of children and any of the producers wham are of working age and the elderly of the importance for the purposes of economic planning. نسبة الفئة العمرية Proportion of the age group (00- -4 4سنوات اقتربت من خمس سكان العراق حيث بلغت سنة)Years approached the fifth of Iraq's population reaching Year2007. (17%))Iraq's population young as the percentage of the population in the age group less 15 15 سنــــــــــــــة Year43% (43%)سنة Year2007 2007. whileنسبة السكان في The proportion of the population ofالفئة العمرية Age group1515-64Which represents the proportion of the working age population amounted 56% (56%,57% )للسنوات For years (199 7 1997،,2000 )على التوالي. Respectively. إن The معدل النمو للناتج المحلي الإجمالي خلال مدة الدراسة The growth rate of gross domestic product (GDP) during the study period( 1987-2007 2007بلغ )Amount حوالي About 9.7% 9.7%، ,في حين بلغ معدل نمو السكان في العراق للمدة While the growth rate of the population in Iraq for the period (1987 1987 – - 199 7 1997 )حوالي About 2.7% 2.7% ، ثم سجل ارتفاعا كبير نسبيا للمدة , Then recorded a relatively large increase for the period 1997 (1997– -2007 2007ليسجل )To score (3.1% 3.1%)تقريبا. Almost. Between standard variable analysis (X2) (Category producer) moral, in other whord the, increase in productive class (23.57% (يودي إلى زيادة الناتج المحلي الإجمالي بما مقداره ( Leads to increased GDP by $ ( 1% 1% ). ).